Five-Year-Olds’ and Adults’ Use of Paralinguistic Cues to Overcome Referential Uncertainty - Thacker, Justine M.; Chambers, Craig G.; Graham, Susan A. (Frontiers in Psychology, 2018)
An eye-tracking methodology was used to explore adults’ and children’s use of two utterance-based cues to overcome referential uncertainty in real time. Participants were first introduced to two characters with distinct color preferences. These characters then produced fluent (“Look! Look at the blicket.”) or disfluent (“Look! Look at thee, uh, blicket.”) instructions referring to novel objects in a display containing both talker-preferred and talker-dispreferred colored items. Adults (Expt 1, n = 24) directed a greater proportion of looks to talker-preferred objects during the initial portion of the utterance (“Look! Look at…”), reflecting the use of indexical cues for talker identity. However, they immediately reduced consideration of an object bearing the talker’s preferred color when the talker was disfluent, suggesting they infer disfluency would be more likely as a talker describes dispreferred objects. Like adults, 5-year-olds (Expt 2, n = 27) directed more attention to talker-preferred objects during the initial portion of the utterance. Children’s initial predictions, however, were not modulated when disfluency was encountered. Together, these results demonstrate that adults, but not 5-year-olds, can act on information from two talker-produced cues within an utterance, talker preference and speech disfluencies, to establish reference.